Design of Lightweight Authentication and Key Agreement Protocol for Vehicular Ad Hoc Networks - Mohammad Wazid; Ashok Kumar Das; Neeraj Kumar; Vanga Odelu; Alavalapati Goutham Reddy; Kisung Park; Youngho Park (IEEE Access, 2017)
Due to the widespread popularity in both academia and industry, vehicular ad hoc networks (VANETs) have been used in a wide range of applications starting from intelligent transportation to e-health and itinerary planning. This paper proposes a new decentralized lightweight authentication and key agreement scheme for VANETs. In the proposed scheme, there are three types of mutual authentications: 1) between vehicles; 2) between vehicles and their respective cluster heads; and 3) between cluster heads and their respective roadside units. Apart from these authentications, the proposed scheme also maintains secret keys between roadside units for their secure communications. The rigorous formal and informal security analysis shows that the proposed scheme is capable to defend various malicious attacks. Moreover, the ns-2 simulation demonstrates the practicability of the proposed scheme in VANET environment.